Hubungan Faktor Lingkungan Fisik Dengan Distress Pada Pekerja Manufaktur - Tanjung, Muhamad Fajar Maulidi; Setiyono, Andik; Dewi, Siti Nurmala (Yayasan Jompa Research and Development, 2025)
Work-related stress is recognized as a global issue that affects all professions in developed and developing countries and is a major challenge to occupational safety and health. Stress is divided into two types: eustress and distress. Negative stress or distress is a reaction to stressors that manifest itself in negative psychological conditions (e.g., anger, emotions, negative thoughts). The objective of this study is to determine the association between physical work environment factors and distress among workers in the hotpressing area of a manufacturing company. This study will be conducted using a quantitative approach and a cross-sectional study design. The population and sample of this study are workers in the hotpressing area of a manufacturing company with a total of 246 respondents. The analysis of this study uses logistic regression testing. The results of the study show that there is an association between the work environment and work distress (p=0.001). Physical environmental conditions such as lighting (p=0.037), humidity (p=0.011), air circulation (p=0.005), and air quality (p=0.005) have a significant or dominant association that affects worker distress, with the variable of exposure protection conditions from hazardous materials being controlled (p=0.415). Distress caused by poor physical environmental conditions results in physiological disorders such as increased heart rate. Meanwhile, the emotional disorders caused by these conditions include workers feeling emotionally exhausted. Cognitive disorders caused by these conditions include workers finding it difficult to concentrate. Furthermore, behavioral disorders caused by these conditions include workers having difficulty sleeping and exhibiting abnormal eating behaviors. These findings serve as a reminder and input for companies that the physical environment at the workplace should not be neglected and must be controlled to ensure it is safe and comfortable for workers, as it will have an impact on their health, especially in terms of disruptive stress or distress.